EU climate policy: Dividing up the commons - Juan Delgado (Bruegel, 2007)
Juan Delgado discusses the economic impact of climate change policies. The EU has committed to an ambitious climate change agenda. The challenge facing Europe now is how to meet the targets at a minimum cost and how to allocate the cost in such a way that it has a neutral impact on competitiveness. This note was presented in August 2007 to the Economic Policy Committee of the EU.
Keywords: 330; Klimaveränderung; EU-Umweltpolitik; EU-Staaten